Evidence mapping and quality assessment of systematic reviews on exercise intervention for Alzheimer's disease - Zhengdong Xu; Jiaxing Tang; Wenjuan Yi (Elsevier, 2024)
Background: A significant body of literature suggests that exercise can reverse cognitive impairment and ameliorate somatic function in patients with Alzheimer's disease (AD). Systematic reviews (SRs), a common approach of evidence-based medicine, concentrate on a specific issue of a research area. The objective of this work is to provide an overview of existing evidence on the effects of exercise intervention in AD patients and report related health outcomes by reviewing SRs. Methods: SRs on exercise intervention in AD patients were retrieved from the PubMed, the Cochrane Library, CBMdisc, Scopus, Web of Science, Embase (via Ovid), China National Knowledge Infrastructure, and WanFang databases from the time of inception to February 2023. The quality of the SRs was evaluated utilizing the A Measurement Tool to Assess Systematic Review 2 (AMSTAR 2) checklist. The results were reported according to the population-intervention-comparison-outcome (PICO) framework and the corresponding evidence mapping was illustrated in tables and bubble plots. Results: A total of 26 SRs met the eligibility criteria. In terms of methodological quality, 10 SRs were rated as ''critically low'', 13 SRs were rated as ''low'', and 3 SRs were rated as ''moderate''. Exercise was found to exert a beneficial effect on cognitive function, functional independence, physical function, and neuropsychiatric symptoms in patients with AD. Conclusion: Exercise intervention benefits AD patients mainly by improving cognitive function, physical function, functional independence, and neuropsychiatric symptoms. However, due to the low-to-moderate methodology of most SRs included in this analysis, further investigations are required to support our current findings.